2015
DOI: 10.1007/s10152-015-0434-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cephalopod species from the North and Baltic Seas using morphology, COI and 18S rDNA sequences

Abstract: We morphologically analyzed 79 cephalopod specimens from the North and Baltic Seas belonging to 13 separate species. Another 29 specimens showed morphological features of either Alloteuthis mediaor Alloteuthis subulata or were found to be in between. Reliable identification features to distinguish between A. media and A. subulata are currently not available. The analysis of the DNA barcoding region of the COI gene revealed intraspecific distances (uncorrected p) ranging from 0 to 2.13 % (average 0.1 %) and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 35 publications
(57 reference statements)
6
15
0
Order By: Relevance
“…Other species, such as the cephalopod Sepiola tridens detected during all seasons, especially around Helgoland, were not expected where we detected them. Studies have already reported that this species has been overlooked in the North Sea 40 , 56 and is often wrongly identified as the morphologically similar S . atlantica , which we found only once But S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other species, such as the cephalopod Sepiola tridens detected during all seasons, especially around Helgoland, were not expected where we detected them. Studies have already reported that this species has been overlooked in the North Sea 40 , 56 and is often wrongly identified as the morphologically similar S . atlantica , which we found only once But S .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, combination of the two gene analyses also revealed similarities in the numbers of species and sequences detected, especially for arthropods and Cnidaria, as already outlined for samples around Helgoland. We benefit from the existence of comprehensive reference datasets for 18S and COI, especially in the cases of calanoid copepods 34 , the common jellyfish genus Cyanea 36 , and cephalopods 40 . Furthermore, both analyses giving different information but shown to be significant at seasonality.…”
Section: Discussionmentioning
confidence: 99%
“…Three classes of molluscs known from the North Sea were not represented in this study: Solenogastres and Caudofoveata are represented in the North Sea by three species each, but none of these was found in the sampled areas; cephalopods were collected, and the results of their study are available elsewhere (Gebhardt & Knebelsberger ).…”
Section: Methodsmentioning
confidence: 99%
“…In order to infer the taxonomic level of the sequences that showed a BLAST homology below 98%, a phylogenetic tree was built with the following sequences: nine GenBank sequences (Groenenberg et al, 2009;Gebhardt & Knebelsberger, 2015) of sepiolids previously reported in the Eastern Atlantic (Sepiola affinis AY293716, Sepiola aurantica AF035708, Sepietta obscura AY293723, Sepiola intermedia AF035709, Sepiola rondeleti AY293720, Sepietta oweniana FJ231297, Sepiola robusta AF035711, Rossia macrosoma KM517936 and Stoloteuthis leucoptera AF000068). In addition, one sequence of Heteroteuthis dispar from our reference library and the haplotypes obtained in our samplings were used.…”
Section: Sample Collectionmentioning
confidence: 99%